Differential expression of adenine nucleotide converting enzymes in mitochondrial intermembrane space: a potential role of adenylate kinase isozyme 2 in neutrophil differentiation. - Ayako Tanimura; Taigo Horiguchi; Keiko Miyoshi; Hiroko Hagita; Takafumi Noma (PLoS ONE)
Adenine nucleotide dynamics in the mitochondrial intermembrane space (IMS) play a key role in oxidative phosphorylation. In a previous study, Drosophila adenylate kinase isozyme 2 (Dak2) knockout was reported to cause developmental lethality at the larval stage in Drosophila melanogaster. In addition, two other studies reported that AK2 is a responsible gene for reticular dysgenesis (RD), a human disease that is characterized by severe combined immunodeficiency and deafness. Therefore, mitochondrial AK2 may play an important role in hematopoietic differentiation and ontogenesis. Three additional adenine nucleotide metabolizing enzymes, including mitochondrial creatine kinases (CKMT1 and CKMT2) and nucleoside diphosphate kinase isoform D (NDPK-D), have been found in IMS. Although these kinases generate ADP for ATP synthesis, their involvement in RD remains unclear and still an open question. In this study, mRNA and protein expressions of these mitochondrial kinases were firstly examined in mouse ES cells, day 8 embryos, and 7-week-old adult mice. It was found that their expressions are spatiotemporally regulated, and Ak2 is exclusively expressed in bone marrow, which is a major hematopoietic tissue in adults. In subsequent experiments, we identified increased expression of both AK2 and CKMT1 during macrophage differentiation and exclusive production of AK2 during neutrophil differentiation using HL-60 cells as an in vitro model of hematopoietic differentiation. Furthermore, AK2 knockdown specifically inhibited neutrophil differentiation without affecting macrophage differentiation. These data suggest that AK2 is indispensable for neutrophil differentiation and indicate a possible causative link between AK2 deficiency and neutropenia in RD.